2014
DOI: 10.1007/s10719-014-9540-z
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a class II α-Mannosidase from Moringa oleifera seed kernels

Abstract: α-Mannosidase (EC. 3.2.1.114) belonging to class II glycosyl hydrolase family 38 was purified from Moringa oleifera seeds to apparent homogeneity by conventional protein purification methods followed by affinity chromatography on Con A Sepharose and size exclusion chromatography. The purified enzyme is a glycoprotein with 9.3 % carbohydrate and exhibited a native molecular mass of 240 kDa, comprising two heterogeneous subunits with molecular masses of 66 kDa (α-larger subunit) and 55 kDa (β-smaller subunit). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Similar results were described by Tejavath & Nadimpalli (2014) and Jain et al (2019), who presented higher values of protein extraction and enzymatic activity, respectively, at temperature of 50 °C; below 50 °C, protein extraction and enzymatic activity increased with increasing temperature. Increases in temperature are responsible for protein folding and structural changes, which are processes that may have affected the protein concentration.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were described by Tejavath & Nadimpalli (2014) and Jain et al (2019), who presented higher values of protein extraction and enzymatic activity, respectively, at temperature of 50 °C; below 50 °C, protein extraction and enzymatic activity increased with increasing temperature. Increases in temperature are responsible for protein folding and structural changes, which are processes that may have affected the protein concentration.…”
supporting
confidence: 88%
“…However, according to Ghebremichael et al (2005), protein is thermoresistant after treatment for 5 h at 95 °C. A recent study showed a drastic reduction in protein extraction at temperatures from 70 °C (Jain et al, 2019) and in enzymatic activity at temperatures from 80 °C (Tejavath & Nadimpalli, 2014). According to Jain et al (2019), this is due to protein denaturation.…”
mentioning
confidence: 99%
“…The importance of M. oliefera plant and its seed material as an interesting source to study various aspects of phytochemistry, proteins and medicine has been growing over the past few years (45). Our laboratory also has isolated and purified from the seeds of this plant a coagulant protein MoCP and also raised an antibody for the same (38) additionally a α-mannosidase was also purified from the seeds and biochemically characterized (46).Our recent interest has also been to explore and identify what components in some seed materials are involved in removing metals from aqueous solutions. As a first step towards this, we recently characterized the proteins and polysaccharides from Strychnos potatorum seeds (31).…”
Section: Discussionmentioning
confidence: 99%
“…Lectins are proteins that interact reversibly and selectively with specific residues of carbohydrates present in glycoconjugates . This specificity of lectins for a particular carbohydrate provides the basis for probing different types of glycoproteins from complex mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Lectins are proteins that interact reversibly and selectively with specific residues of carbohydrates present in glycoconjugates. 32 This specificity of lectins for a particular carbohydrate provides the basis for probing different types of glycoproteins from complex mixtures. Concanavalin A (Con A), a lectin from Canavalia ensiformis or Canavalia gladiate, has found broad use in the purification of several glycopreins.…”
Section: Introductionmentioning
confidence: 99%